The Impact of Production Technologies Used in the Beef Cattle Industry - Matt Hersom; Todd Thrift; Joel Yelich (EDIS)
The use of technologies in the beef industry is a major contributor to the safe, wholesome, and affordable beef supply in the United States. This 4-page fact sheet provides a brief evaluation of the effects that individual technologies have on beef production. Written by Matt Hersom, Todd Thrift, and Joel Yelich, and published by the UF Department of Animal Science, September 2011.